Tornadoes - Simon, Seymour (New York : scholastic, 2011)
20 science vocabulary words...Describes the location, nature, development, measurement, and destructive effects of tornadoes, as well as how to stay out of danger from them.
6.4
K-3
Keywords: Tornadoes -- Juvenile literature; Tornadoes; Tornadoes